Genetic condition of human papillomavirus high carcinogenic risk - Zhumasheva, K.A.; Pogossyan, G.P.; Zhumashev, B.K.; Danilenko, M. (Fundamental and Experimental Biology, 2020)
The authors consider the basic concepts of HPV-induced carcinogenesis and the molecular differences found among types of HPV and intra-type variants, and give their clinical and functional consequences. Human papillomavirus (HPV) is a diverse group of small DNA viruses, some of which have been extensively studied over the past three decades due to their carcinogenic potential. The persistence of viral infections and the uncontrolled expression of the E6 and E7 viral oncogenes are critical events in the transformation process. It is important to note that viral types are specific for each type of cell and usually cause various types of lesions, benign or malignant. Recognizing the critical role that certain specific types of HPV play in the development of cervical cancer is very important for their prevention and public health strategies for cervical cancer, which are still the leading cause of death among cancer patients in many countries.